Digital Finance and Risk Dynamics: A Study of Xiaomi's Supply Chain Innovations - Liu, Lihao; Bi, Haoran; Sun, Hao; Wang, Jiamin; Zhang, Du (Transactions on Economics, Business and Management Research, 2024)
With the rise of the digital economy, online supply chain finance has become a vital avenue for corporate financing. This paper takes Xiaomi as a case study to explore the risk management issues in online supply chain finance. The article begins with an overview of the basic concepts of online supply chain finance and Xiaomi's unique position in this field. Subsequently, it analyzes the main types of risks faced by Xiaomi, including credit risk, market risk, and operational risk, and discusses how these risk factors affect the company's supply chain finance activities. The paper further explores Xiaomi's management strategies in risk assessment, prevention, and control, as well as how to leverage technological means such as big data, blockchain, and artificial intelligence to enhance risk management capabilities.